Manajemen Peserta Didik dalam Meningkatkan Prestasi Akademik Siswa Pasca Pandemi Covid-19 - Ihsani, Qidam Anwarul; Munawaroh, Mumun; Mukhlisoh, Mukhlisoh (Universitas Islam Negeri Raden Intan Lampung, 2023)
The presence of the Covid-19 pandemic has made the quality of education tend to decline. However, something unique happened at MAN 3 Cirebon, in fact, the academic achievement of students increased rapidly after the Covid-19 pandemic because of good student management. The purpose of this study is to describe the planning, implementation, supervision, and provide an overview of students' academic achievement after the Covid-19 pandemic at MAN 3 Cirebon. This study was designed using descriptive qualitative methods with a phenomenological approach. Data collection was conducted using moderate participation observation techniques, in-depth interviews, and documentation studies. Data analysis procedures through the stages of data collection, data reduction, data presentation, and drawing conclusions. While testing the validity of this research data using source triangulation and triangulation techniques. Based on the research that has been done, it can be seen that MAN 3 Cirebon carries out diagnostic activities, policy formulation, and prioritization at the student management planning stage. At the stage of implementing student management, MAN 3 Cirebon conducts activities to accept new students, coach students, and evaluate students. Then, MAN 3 Cirebon also conducts simultaneous supervision which is carried out directly and indirectly. This was done very well by MAN 3 Cirebon so that it experienced a significant increase in academic achievement after the Covid-19 pandemic.